Weaponizing Sovereignty: Hungary’s Protection of National Sovereignty Act and the Erosion of Fundamental Rights - Setyo Widagdo; Fransiska A. Susanto; Anak Agung Ayu Nanda Saraswati (Universitas Negeri Surabaya, 2026)
On November 21, 2023, Hungarian Prime Minister Viktor Orban, leader of the Fidesz Party, submitted Act LXXXVIII of 2023 on the Protection of National Sovereignty to fight what he described as unwarranted political intervention by foreigners or specialised organisations. The SPO's major task is to